IMPLEMENTING MERIT-BASED POSITION PROMOTIONS IN MALANG DISTRICT, EAST JAVA PROVINCE - Amalia, Rizki; Selamat, Mohd. Nasir; Ekowati, Maria; Fatimah, Yeti; Nangameka, Teresa Irmina (Institut Pemerintahan Dalam Negeri, 2024)
The merit system stands as a cornerstone in human resource management, emphasizing qualifications, competencies, and performance across various facets such as planning, recruitment, payroll, development, promotion, retention, discipline, and retirement of employees. However, the implementation of this system within the Malang Regency Government reveals gaps, particularly in the fulfillment of positions, notably within sub-districts and kelurahans. This research delves into the challenges surrounding the promotion of civil servants in echelon III and IV positions based on the merit system. The aim is to scrutinize the promotion process and Strategies adopted by the Malang Regency government, East Java Province. Employing a qualitative approach with a case research method, primary data is gathered from interviews with informants, complemented by secondary data derived from documentation. Through techniques such as interviews, documentation, and observation, qualitative data analysis is conducted. The promotion strategy is further evaluated using a SWOT analysis, pinpointing strengths, weaknesses, opportunities, and threats. Findings reveal that vacancies in sub-districts stem from employees' educational levels, often limited to high school qualifications, leading to the appointment of personnel through PLT. The Department of Human Resources (BKPSDM) endeavors to incentivize employees to pursue higher education. Notably, nine key indicators—honesty, discipline, work performance, cooperation, proficiency, loyalty, leadership, communication, and education—emerge as crucial in promotion evaluations, though challenges persist, particularly in meeting education and discipline requirements. The SWOT analysis aids in identifying priority programs and activities essential for advancing promotion based on the merit system in Malang Regency, East Java Province.